Accreditation Handbook - Norazzlina, M.Sa'don; Lim, Soh Fong; Syed Tarmizi, Syed Shazali; Sharifah Masniah, Wan Masra; Dayangku Salma, Binti Awang Ismail; Abdul Razak, Abdul Karim; Siti Nor Ain, Hj Musa; Ivy Tan, Ai Wei; Wan Hashim, Wan Ibrahim; Al Khalid, Othman (UNIMAS Publisher, 2012)
This handbook is a reference for the faculty, academic and administrative staff on the process and procedure involved in preparing and obtaining accreditation. This handbook also serves as a valuable guide for the faculty to develop an assessment plan in the process of the future accreditation.